The next ascent : an evaluation of the Aga Khan Rural Support Program, Pakistan - World Bank. (Washington, D.C. : World Bank, 2002)
The fourth independent evaluation by the World Bank of the Aga Khan Rural Support Program in northern Pakistan. The book assesses the development outcome of both the program since its initiation and in the five-year period after the 1995 evaluation.
At head of title: World Bank Operations Evaluation Department.
Includes bibliographical references (p. 137-139).
osa 22/08/16
Loans
Keywords: Rural development; Aga Khan Rural Support Programme; Pakistan